Acculturation of The Application of Inheritance Law in The Sundanese Indigenous Community of Wiwitan - Siti Nuraidah; Ani Yumarni; Nurwati (Indonesian Journal of Social Research (IJSR), 2021)
Indigenous peoples are legal subjects recognized for their traditional rights and other rights by the 1945 Constitution and other laws and regulations. Sunda Wiwitan is understood as the original Sundanese religion or early Sundanese which is the naming of the belief system used by people of Sundanese descent who still confirm the spiritual teachings of the Sundanese ancestors. Humans are legal subjects, bearers of rights and obligations from the moment of birth and end when humans die. From the event of a person's death, there are legal consequences, namely how to resolve the rights and obligations of the person's death which is regulated by inheritance law. This is an empirical juridical method or non-doctrinal study, looking at the validity of a statutory regulation and legal norm originating from religion, which lives and develops in a group of indigenous peoples. The purpose of this study was to determine and examine the acculturation of customary inheritance law and Islamic inheritance law in the Sunda Wiwitan community and to determine the form of application of Islamic inheritance law to the Sunda Wiwitan indigenous people in Kasepuhan Ciptagelar with Kampung Urug. The results show that the acculturation of the application of inheritance law to the Sunda Wiwitan community, Kasepuhan Ciptagelar and Kampung Urug regarding the application of Islamic inheritance law is that Islamic inheritance law is carried out by prioritizing deliberation and consensus in the family of the heirs of the Sunda Wiwitan Indigenous Peoples. followers of Islam. As for customary law, the Sunda Wiwitan people make it a norm and culture that is carried out in social life.